Hakikat Sumber Daya (Fitrah, Akal, Qalb, dan Nafs) Manusia dalam Pendidikan Islam - M. Dwi Rahman Sahbana (Indonesian Institute for Counseling, Education and Theraphy, 2022)
The purpose of this study is to determine the nature of human resources (fitrah, reason, heart and nafs) in Islamic education. The author conducts research using literature study whose subject is literature. The results of the research conducted by the author are that human resources play an important role in the world of education, of course for Muslims, namely in Islamic education. In this study, there are four components of human resources, namely fitrah, reason, qalb, nafs. With these four components, the writer analyzes the essence of Islamic education. The results of this analysis are firstly that human nature is innate from human birth which will eventually become a habit, it can also be interpreted that human nature is to know the oneness of God and understand the religion of Allah, there are four schools that discuss the basic nature and development process, namely, the view of fatalist, neutral view, positive view and dualist view. Both minds are thinking tools possessed by humans as differentiators from other God's creatures, the focal point of the work of reason is the source of thinking in humans to determine or distinguish good and bad things and reason one of its main functions is to strengthen faith in Allah SWT. When the human mind comes from the true knowledge of Islam which is also in accordance with Islamic law, then the human personality is fine, and vice versa. The three hearts are things that are contained in humans that are subtle and function and serve as the deepest sense of all things, both positive and negative. The four nafs are impulses or motivations that exist in humans, the nafs also cannot always be seen as bad in its existence, because even in doing good things, humans involve the nafs in it. So the nafs (urge) will be good if it follows a pure heart and the right mind in accordance with Islamic teachings, while the nafs (urge) will be bad and even misguided if the heart is dirty and reason and bad thoughts dominate in humans. Keywords: Human Resources, (Fitrah, Intellect, Qalb, Nafs), Islamic Education.